Food security: how to deal with effects of climate change on Indian agriculture - Amarnath, Giriraj (2022)
The largest climate hazard risks to state food supply are in Bihar, Madhya Pradesh, and Assam. These most at-risk areas should be prioritised with investments in early warning systems, and sustainable adaptation of agriculture.